TIOLOGI ADAT DAN TRADISI PERNIKAHAN (BAKEJOI) PERSPEKTIF ISLAM DI RAWANG KOTA SUNGAI PENUH - Zuhdi, Ahmad; Gusfitriani, Beti; Fitri, Melta Asrina; Mariani, Mimi; Paryadi, Paryadi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2023)
In the Sungaipuh and Kerinci communities, the term “Adat with Syarak, Syarak with Kitabullah” is known.This is a form of affirmation of the awareness of the people here who are familiar with adat, but adapt it to Islamic religious law. So that in every step of life, traditional processions are not abandoned as long as these steps do not deviate or violate Islamic religious provisions.This attachment to and blend of customs and religious provisions fills every stage of the life of the Hamparan Rawang people.One of the stages in the life of a human child is marriage. Getting married means ending the single period and entering a household with a life partner according to custom, religion and applicable regulations.